2014
DOI: 10.1371/journal.pone.0089401
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Severity and Trait Resilience as Predictors of Posttraumatic Stress Disorder and Depressive Symptoms among Adolescent Survivors of the Wenchuan Earthquake

Abstract: PurposeTo examine the associations between trauma severity, trait resilience, and posttraumatic stress disorder (PTSD) and depressive symptoms among adolescent survivors of the Wenchuan earthquake, China.Methods788 participants were randomly selected from secondary schools in the counties of Wenchuan and Maoxian, the two areas most severely affected by the earthquake. Participants completed four main questionnaires including the Child PTSD Symptom Scale, the Center for Epidemiologic Studies Depression Scale fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
99
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(124 citation statements)
references
References 59 publications
23
99
2
Order By: Relevance
“…Based on the correlational analysis, the result demonstrated that resilience was found to be significantly and negatively correlated with depression. This finding was supported with previous studies reporting the relationship between resilience and depression (Ying et al 2014;Spies & Seedat 2014;Pérez-López et al 2014;Hjemdal et al 2006). Resilient adolescents view divorce and life in single parent-family as a meaningful and empowering transition (Eldar-Avidan, HajYahia & Greenbaum 2009).…”
Section: Relationship Between Family Functioning Resilience and Deprsupporting
confidence: 88%
“…Based on the correlational analysis, the result demonstrated that resilience was found to be significantly and negatively correlated with depression. This finding was supported with previous studies reporting the relationship between resilience and depression (Ying et al 2014;Spies & Seedat 2014;Pérez-López et al 2014;Hjemdal et al 2006). Resilient adolescents view divorce and life in single parent-family as a meaningful and empowering transition (Eldar-Avidan, HajYahia & Greenbaum 2009).…”
Section: Relationship Between Family Functioning Resilience and Deprsupporting
confidence: 88%
“…However, there was no significant difference in resilience of males and females in the total sample. Previous studies (Aronen and Kurkela, 1998;Campbell-Sills et al, 2006) have reported the lack of a significant difference in resilience of males and females, while others (Boardman et al, 2008;Stratta et al, 2013;Scoloveno, 2013;Ying et al, 2014) had reported that males were found to report more resilience than females. A number of explanations can be offered with regard to the finding in the current study.…”
Section: Discussionmentioning
confidence: 94%
“…Evidence of gendered psychological resources (e.g., agency, mastery and worth) in favour of males which may provide the requisite foundation to enable resilience characteristics (Shanahan and Hofer, 2005) have been supported by studies showing higher resilience in adolescent males compared to females (Campbell-Sills et al, 2009;von Soest et al, 2010;Waaktaar and Torgersen, 2012;Abukari and Laser, 2013;Stratta et al, 2013;Ying et al, 2014). Among older populations, males have also been found to report higher resilience (Boardman et al, 2008).…”
Section: Gender and Resiliencementioning
confidence: 99%
“…This scale has 17 items rated on a 4-point Likert scale from 0 (not at all/only once) to 3 (almost always). This scale was applied to the Chinese population with good validity and reliability (Ying, Wu, & Chen, 2013; Ying, Wu, Lin, & Jiang, 2014). In the current study, all items were translated into Chinese.…”
Section: Methodsmentioning
confidence: 99%